A flexible model of term-structure dynamics of commodity prices: A comparative analysis with a two-factor Gaussian model - Suenaga, Hiroaki (2015)
This book covers the fundamental theory of and derivatives pricing for major commodity markets as well as the interaction between commodity prices and the real economy and other financial markets.